ANALISIS KESALAHAN BERBAHASA PADA ORASI KETUA BEM UNIVERSITAS INDONESIA DALAM ACARA MATA NAJWA “KARTU KUNING JOKOWI” - Tri Mardani (Faculty of Economics, Law, and Humanities, 2020)
This paper describes the analysis of oral language errors committed by the chairman of BEM UI (Zaadit Taqwa) in Mata Najwa's event on February 7, 2018 in one of the private TV stations in Indonesia. The provision of data in this study was obtained by examining oral utterances that have been transcribed in written form with recording techniques, references, and notes. Recorded data, is speech orasi in the event Mata Najwa with some other sources. Recording using paper and pen, while recording using DU RECORDER application on Samsung Galaxy E5 mobile phone. The results of the study were then analyzed to find the errors in the oral speech. After data analysis, transcript matching with video from various sources was done to ensure more accurate result of analysis and to dig deeper about error of speech presented by BEM UI chairman at Mata Najwa event. Not only in the speeches, but in the question and answer session with some speakers also transcribed. The results of this study indicate that there are some speech errors and language disturbances conducted by informants, such as mistakes in public speaking law regarding information clarity, morphological errors, tongue lightning, silence and hoax phenomena are busy discussed in the community